Synergistic effects of Zoledronic acid and Quercetin in vitro on breast cancer cells migration, proliferation and viability - Alsawalha, Laila; Al-Groom , Rania; Rammaha , Majdolen; Hasan , Diya; Masadeh, Muhannad I.; Abaza , Sara (Acta Biomedica Atenei Parmensis, 2026)
Background and aim of the work: Quercetin: a natural bioactive molecule has showed promise in cancer prevention and treatment. It is used for various cancers including breast cancer. The bisphosphonate Zoledronic acid (ZA); has recently come into therapeutic use. Despite the introduction of several medicinal techniques, breast cancer remains the most common uncurable cancer in women. Given this, the current study aims to elucidate the synergistic antitumor interaction between quercetin and zoledronic acid; both of which have anti-proliferative and anti-metastatic capabilities , notably targeting fatty acid synthesis and cholesterol synthesis in breast cancer cells in vitro.Research design and methods: Human breast cancer cell lines MCF-7  and MDA-MB-231 were treated with a quercetin, ZA, or their combination. Quercetin was applied at concentrations of 480, 240, 120, 60, 30, and 10 μM, and ZA at 360, 160, 80, 40, 20, and 10 μM. Combination treatments were applied using 80:80, 180:80, and 80:160 μM for MCF-7 cells, and 90:171, 180:171, 90:340 μM for MDA-MB-231 cells. Cell proliferation was assessed using the MTT cytotoxicity assay. RT-PCR was performed to analyze the expression of genes linked to apoptosis, clone creation, and cell migration.Results: The quercetin-ZA combination induced Bcl-2-independent apoptosis and significantly inhibited cell growth.. The combined treatment was more effective than either medication alone after 72 hours, with IC50 values of 80:160 μM for MCF7 (p=0.0021) and 90:171 μM for MDA-MB-231 cells (p=0.0161). Self-renewal and clonogenic tumor development were markedly inhibited after 3-hour combination treatment. Moreover, MCF7 and MDA-MB 231 cell invasiveness was significantly decreased from 24 to 72 h compared with untreated cells.Conclusions: The quercetin-ZA combination synergistically suppressed MCF-7 and MDA-MB-231 breast cancer cells, reducing migration and self-renewal. These findings highlighted their potential adjuvant effects on conventional treatments of breast cancer.